Recurrent Cervical Cancer Treated Successfully with Single-Agent PARP-Inhibitor, Olaparib - Maya Gross; Ryan J. Spencer (Hindawi Limited, 2022)
Recurrent cervical cancer has a grim prognosis with 5-year survival <5%. Current treatment options are limited; standards of care such as palliative chemotherapy and surgical resection often provide a small survival advantage. To date, only one targeted agent has FDA approval for the treatment of recurrent cervical cancer. We present the case of a novel application of olaparib, a poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitor, as single-agent therapy for recurrent metastatic clear cell cervical cancer in a patient with a somatic BRCA2 mutation. The patient had excellent response to therapy with stable disease without evidence of progression until 14 months of therapy, at which time she was switched to an alternative regimen.